Exposure to an Extended-Interval, High-Dose Gentamicin Regimen in the Neonatal Period Is Not Associated With Long-Term Nephrotoxicity - Rypdal, Veronika; Jørandli, Sondre; Hemmingsen, Dagny; Solbu, Marit Dahl; Klingenberg, Claus (Frontiers in Pediatrics, 2021)
Objectives: To assess the association between gentamicin exposure and subclinical signs of nephrotoxicity in schoolchildren who were exposed to a high-dose gentamicin regimen in the neonatal period. Methods: Children receiving three or more doses (6 mg/kg) of gentamicin as neonates were invited to a follow-up in school age. We evaluated potential signs of subclinical nephrotoxicity with four validated urine biomarkers: protein-creatinine ratio (PCR), albumin-creatinine ratio (ACR), kidney injury molecule-1 (KIM-1) and N-acetyl-beta-D-glucosaminidase (NAG) normalized for urine creatinine (NAG-Cr). In addition, blood pressure was measured. The measures of gentamicin exposure were cumulative dose (mg/kg) and highest trough plasma concentration (TPC) in mg/L. We used logistic and linear regression and nonparametric kernel regression to analyze the relationship between gentamicin exposure and the urine biomarkers. Results: A total of 222 gentamicin exposed children were included. As neonates, the children were exposed to a median (interquartile range-IQR) cumulative gentamicin dose of 36 (24-42) mg/kg and the median (IQR) TPC was 1.0 (0.7-1.3) mg/L. At follow-up, 13 children (5.9%) had one abnormal urine biomarker value, and two children (0.9%) had two abnormal urine biomarker values. In all cases, the biomarker values were marginally above the suggested upper cutoff. All other 207 children had normal sets of all four urine biomarkers. One child had hypertension. There were no differences in gentamicin exposure, gestational age at birth or birth weight between the group of 15 children with one or two abnormal urine biomarker values compared to the other 207 children who had normal biomarker values. Using different regression analyses, we did not find any association between gentamicin exposure (cumulative dose and/or TPC) and the urine biomarker values. Conclusions: Exposure to a high-dose gentamicin regimen in the neonatal period was not associated with signs of subclinical nephrotoxicity in schoolchildren. We therefore suggest that the gentamicin treatment regimen evaluated in this study is safe in terms of long-term nephrotoxicity.